The Effect of China on ASEAN: The BRI Projects in Myanmar - Ali Demir (Andalas Institute of International Studies, 2022)
This article focuses on China's gaining favourable approaches in ASEAN as a result of its investment in BRI projects within ASEAN countries. The study tries to explain both how China-Myanmar bilateral relations have developed and how Myanmar's position in ASEAN can be a possible